Unsafe Abortion a Neglected Tragedy - Vaidya, Achala; Giri, A (Journal of Nepal Health Research Council, 2009)
Not uploaded. Key words: Abortion; Exploration; Pelvic peritonitis; trimestir; Unsafe abortion DOI: 10.3126/jnhrc.v6i1.2438 Journal of Nepal Health Research Council Vol. 6, No. 1, Issue 12, April, 2008 Page: 11-15